2017
DOI: 10.1111/wrr.12561
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapies and their effects on wound healing

Abstract: Oxygen is an important factor for wound healing. Although several different therapies investigated the use of oxygen to aid wound healing, the results of these studies are not unequivocal. This systematic review summarizes the clinical and experimental studies regarding different oxygen therapies for promoting wound healing, and evaluates the outcomes according the methodological details. A systematic literature search was conducted using Embase, Medline, Web of Science, Cochrane, PubMed publisher, and Google … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 84 publications
(324 reference statements)
2
71
0
2
Order By: Relevance
“…45 Many patients with DFUs have impaired oxygenation to wounded areas, especially in the setting of vascular disease. Therapeutic strategies to correct this include local delivery of oxygen to the wound and systemic oxygen administration.…”
Section: Oxygen Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Many patients with DFUs have impaired oxygenation to wounded areas, especially in the setting of vascular disease. Therapeutic strategies to correct this include local delivery of oxygen to the wound and systemic oxygen administration.…”
Section: Oxygen Therapiesmentioning
confidence: 99%
“…This mode of treatment has been studied primarily in surgical wounds and has not been well studied in DFUs. 45 Hyperbaric oxygen (HBOT) is administered in a compression chamber, which provides 100% oxygen and delivers a greatly increased partial pressure of oxygen to tissues. A 2015 Cochrane review that pooled data from 10 RCTs showed that there was a significant increase in rate in healing with HBOT at 6 weeks, although this benefit was not evident at follow-up at 1 year.…”
Section: Oxygen Therapiesmentioning
confidence: 99%
“…In fact, Qu by itself has strong antimicrobial and antioxidant activity, [29][30][31] while AO increases the expression of vascular endothelial growth factoralpha (VEGF-α) and interleukin-1beta (IL-1ÎČ). 32 Finally, several authors documented that the treatment of DFUs accounts for approximately one-third the total cost of diabetic care, 33 but only few patients, about 20%, have unhealed DFUs at 1 year 34,35 and about 40% have a recurrence in 1 year. 18 Even if in our study we do not performed an economic evaluation, we can affirm that the topical treatment was performed at home and did not require other treatment or hospitalisation, and also no recurrence occured, suggesting that this treatment could be cost/saving.…”
Section: Copd 15 14mentioning
confidence: 99%
“…Molecular oxygen is also necessary for collagen synthesis during the remodelling phase. 23 Diabetic hyperglycaemia can negatively affect the microvasculature by causing endothelial cell damage, causing abnormal vascular function, reducing perfusion, and decreasing oxygen and nutrient delivery to the wound. 24 As such, the ability to monitor parameters related to tissue oxygenation has the potential utility to non-invasively assess healing.…”
Section: Oxygen In Wound Healingmentioning
confidence: 99%
“…During the inflammatory phase, oxidant levels increase via Nicotinamide adenine dinucleotide phosphate (NADPH)‐linked oxygenase, consuming high amounts of oxygen, and oxygen limitation can prolong the inflammatory phase. Molecular oxygen is also necessary for collagen synthesis during the remodelling phase …”
Section: Introductionmentioning
confidence: 99%